Cleaning of Dust between Interactive Contact Surfaces by Application of Normal Loads of Artificial Stainless-Cantilever in AFM - SeungChol CHOI; Mikio HORIE; Yasuhisa ANDO (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2007)
In this study, we investigated that interactive contact surfaces were affected by dust and applied normal loads of cantilever such as bristles. In order to study the effect of interactive contact surfaces, spherical particles (dry borosilicate glass sphere, plastic sphere) with curvature radius (R=5 μm, R=10 μm) were glued to artificial stainless cantilevers (spring constant k=576.7 N/m). The experiments were performed on various normal applied loads using an AFM (Atomic force microscope). The results indicate that spheres with a small curvature radius removed dust more effectively than did either of those with a large curvature radius, abraded by using the stainless cantilever, over the wide contact area (50 μmx50 μm). The plastic spheres tend to deform more than do the borosilicate glass spheres under the same applied load and the spheres with a smaller curvature radius tend to deform than do those with a larger curvature radius and the same material properties. Therefore, it had an influence on interactive surface forces. Restructuring dust aggregates by sliding a cantilever, as well as applying loads and contact pressure, forms a new micro contact area, which influences micro surface forces.